Preparation of Polyfunctional Naphthyridines by Cobalt-Catalyzed Cross-Couplings of Halogenated Naphthyridines with Magnesium and Zinc Organometallics - Greiner, Robert (Org Lett, 2017)
[Image: see text] CoCl(2) (5%) catalyzes cross-couplings of various halogenated naphthyridines with alkyl- and arylmagnesium halides. Also, arylzinc halides undergo smooth cross-couplings with various naphthyridines in the presence of CoCl(2)·2LiCl (5%) and sodium formate (50%), leading to polyfunctional arylated naphthyridines. Two of these arylated naphthyridines are highly fluorescent, with quantum efficiencies reaching 95% and long excited-state lifetimes of up to 12 ns.